The level of C‐reactive protein in chronic hemodialysis patients: A comparative study between patients with noninfected catheters and arteriovenous fistula in two large Gulf hemodialysis centers. Issue 3 (27th January 2014) - Sabry, Alaa A.; Elshafey, Eid M.; Alsaran, Khalid; Shalaby, Medhat; Alsherbeiny, Sherrine; Abdelkader, Mohamed
Abstract Hemodialysis (HD) patients have greater morbidity and mortality when they have a central venous catheter (CVC) rather than an arteriovenous fistula (AVF) access. Inflammation associated with dialysis catheter use and resultant higher C‐reactive protein (CRP) levels could have an independent adverse effect on patient outcomes. In this prospective study, we investigated whether HD catheters induce inflammation independent of infection. We compared the mean levels of the inflammatory marker (CRP) in 67 patients on maintenance HD using noninfected catheters with 86 HD patients using AVFs at Prince Salman Center for Kidney Diseases, Saudi Arabia (KSA), and Jahra Hospital, Kuwait, who met our inclusion criteria. C‐reactive protein levels were measured every 2 months over a period of 6 months using immunoturbidimetric assay. One hundred fifty‐three patients on maintenance HD for more than 6 months were included in the study, with mean age of 52.19 ± 16.06 years; 66% were males and 34% were females. Serial levels of mean CRP were statistically and significantly higher in group with noninfected catheters (1.33, 1.24, and 1.10 mg/dL) compared to those with AVFs (0.65, 0.59, and 0.68 mg/dL) with P value of 0.000. In our study, we found no relation between CRP level and age, sex, hemoglobin, albumin, calcium, phosphorus, and iPTH level in both groups. Hemodialysis patients with a catheter have a heightened state of inflammation independent of infection, and thus our study supports the avoidance of catheters and a timely conversion to AVFs with catheter removal.